2007
DOI: 10.1029/2006jg000283
|View full text |Cite
|
Sign up to set email alerts
|

Searching for microbial life remotely: Satellite‐to‐rover habitat mapping in the Atacama Desert, Chile

Abstract: [1] The Atacama Desert, one of the most arid landscapes on Earth, serves as an analog for the dry conditions on Mars and as a test bed in the search for life on other planets. During the Life in the Atacama (LITA) 2004 field experiment, satellite imagery and ground-based rover data were used in concert with a 'follow-the-water' exploration strategy to target regions of biological interest in two (1 coastal, 1 inland) desert study sites. Within these regions, environments were located, studied and mapped with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 34 publications
(46 reference statements)
0
34
0
Order By: Relevance
“…Because of the altitude and latitude of these sites, a number of environmental parameters similar to those of ancient Mars are present together and include a low average temperature, high-daily temperature variations, thin atmosphere, high solar irradiance, ice, reduced yearly precipitation, and a volcanic and hydrothermal environment. Because of this unique set of conditions, NASA-funded researchers undertook an extensive study in preparation for the search for life on Mars (e.g., [67,68]). In the Chilean Andes, near the Atacama Desert, is located the geothermal site of El Tatio, the largest geyser field in the southern hemisphere.…”
Section: Hydrothermalism: Martian Environmentsmentioning
confidence: 99%
“…Because of the altitude and latitude of these sites, a number of environmental parameters similar to those of ancient Mars are present together and include a low average temperature, high-daily temperature variations, thin atmosphere, high solar irradiance, ice, reduced yearly precipitation, and a volcanic and hydrothermal environment. Because of this unique set of conditions, NASA-funded researchers undertook an extensive study in preparation for the search for life on Mars (e.g., [67,68]). In the Chilean Andes, near the Atacama Desert, is located the geothermal site of El Tatio, the largest geyser field in the southern hemisphere.…”
Section: Hydrothermalism: Martian Environmentsmentioning
confidence: 99%
“…SPI provided the intermediate scale in contextual imaging, between the global satellite imagery and the local‐to‐microscopic scale obtained from the fluorescence imager. This scaling continuum and nested imagery was critical in the evaluation of the presence of oases at metric to micrometric scale [ Warren‐Rhodes et al , 2007a, 2007b]. The SPI imager was also used to detect atmospheric changes, specifically the presence of morning and late afternoon fog events in the Coastal Range (as shown at Site A in Figure 1), which signaled the location of potential water accumulation on the ground and, possibly, the concentration of life.…”
Section: Rover and Science Payloadmentioning
confidence: 99%
“…The FI was used to identify several possible biosignatures [ Cabrol et al , 2005; Wettergreen et al , 2005a, 2005b; Weinstein et al , 2006, also submitted manuscript, 2007; Warren‐Rhodes et al , 2005, 2007a, 2007b]. Chlorophyll was checked by the addition of water to the targets through direct spray.…”
Section: Rover and Science Payloadmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to acquire fluorescence data in daylight provided the LITA team a tool to potentially map life over large regions as the rover traveled throughout each day. The results of this aspect of the field study are reported by Warren‐Rhodes et al [2007a, 2007b]. More research is required to perfect the dye probes and probe penetration for optimal use.…”
Section: Discussionmentioning
confidence: 99%